Computational Chemistry - Harvey, Jeremy (New York Oxford University Press, 2018)
The powerful and versatile applications of computational chemistry are covered succinctly and clearly in this primer, making it an ideal introduction for those new to the field. The renowned Oxford Chemistry Primers series, which provides focused introductions to a range of important topics in chemistry, has been refreshed and updated to suit the needs of today's students, lecturers, and postgraduate researchers. The rigorous, yet accessible, treatment of each subject area is ideal for those wanting a primer in a given topic to prepare them for more advanced study or research. The learning features provided, including exercises at the end of every chapter and online multiple-choice questions, encourage active learning and promote understanding. Moreover, cutting-edge examples and applications throughout the texts show the relevance to current research and industry of the chemistry being described. Computational Chemistry provides a user-friendly introduction to this powerful way of characterizing and modelling chemical systems. This primer provides the perfect introduction to the subject, leading the reader through the basic principles before showing the variety of ways in which computational chemistry is applied in practice to study real molecules, all illustrated by frequent examples. Online Resource Centre The Online Resource Centre to accompany Computational Chemistry features: For registered adopters of the text: Figures from the book available to download For students: Full worked solutions to the end-of-chapter exercises Multiple-choice questions for self-directed learning.
Include Index
Keywords: Chemistry--Data processing -- Chemistry--Computer simulation -- Chemistry--Mathematics